Moral Theology in India Today: The DVK National Workshop on Moral Theology - Tirimanna, Vimal (Asian Horizons, 2013)
Shaji George Kochuthara, ed., Moral Theology in India Today. The DVK National Workshop on Moral Theology, Bangalore: Dharmaram Publications, 2013. Pages: 648. ISBN: 978-81-89958-68-8